Bifunctional Silica-Coated Superparamagnetic FePt Nanoparticles for Fluorescence/MR Dual Imaging. (31st May 2012) - Lai, Syu-Ming; Tsai, Tsiao-Yu; Hsu, Chia-Yen; Tsai, Jai-Lin; Liao, Ming-Yuan; Lai, Ping-Shan
Abstract : Recently, superparamagnetic chemically disordered face-centered cubic (fcc) FePt nanoparticles have been demonstrated as superior negative contrast agents for magnetic resonance imaging (MRI). However, their low intracellular labeling efficiency has limited the potential usage and the nanotoxicity of the particles requires attention. We have developed fluorescein isothiocyanate-incorporated silica-coated FePt (FePt@SiO2 -FITC) nanoparticles that exhibited not only a significant T 1 and T 2 MR contrast abilities but also a fluorescent property without significant cytotoxicities. These results suggest that silica-coated superparamagnetic FePt nanoparticles are potential nanodevices for the combination of fluorescence and MRI contrast used for cancer diagnosis.